ปัจจัยพหุระดับที่มีอิทธิพลต่อประสิทธิผลการบริหารงานวิชาการ ของโรงเรียนในสังกัดองค์กรปกครองส่วนท้องถิ่น - ศรีโนนยาง, วรรณที; สร้อยน้ำ, สมคิด; หอมสิน, นวัตกร (Journal of Education Studies, Chulalongkorn University, 2019)
The objectives of this research were 1) to study the level of the school’s academic administrative effectiveness under the Department of Local Administration.2) to find the student-level factors, classroom level factors and school level factors that Influenced and 3) to construct a Multi-level model of factors. The sample comprised 1,380 people. They were 60 administrators, 120 teachers and 1,200 students selected by Multi-stage sampling. The instruments were 4 types of questionnaires: (1) for students, (2) for teachers, (3) for school administrators and (4) questions about school’s academic. The reliability value of the questionnaires were .907, .944, .939 and .941 respectively. The data were analyzed using percentage, mean and standard deviation. Multilevel model was analyzed using HLM program. The results of this research were as follows: 1) The academic administrative effectiveness was at the high level. 2) For the student factors, it was found that the learning attitude, the learningbehavior andthe learning experienceweresignificant at .05, .05 and 01 level respectively. For the classroom factors, it was found that the teaching quality and the teachingexperienceweresignificant at .01 and .05 level respectively.For the school factors, it was found that the instructional leadershipand the administration experienceweresignificant at .01 and .05 level respectively. 3)The multilevel model of factors was illustrated as a mixed model below: ACHIEVE = 4.279**+ 0.045** LEADER - 0.034*EXPER3 + 0.105*QUAL2 + 0.088*EXPERI2 +0.046* ATTITUDE + 0.059*BEHAVE + 0.103BEHAVE* BEHAVE2 - 0.058** EXPERIEN + 0.038* EXPERIEN*EXPER3 + 0.216* EXPERIEN* QUAL2 THE DEPARTMENT OF LOCAL ADMINISTRATION